Lime-based restoration paints: characterization and evaluation of formulations using a native species from the Amazon flora and PVA-based glue as additives - Silva, Mayra Martins; Sanjad, Thais Alessandra Bastos Caminha; Costa, Marcondes Lima da; Costa, Solange Perpétuo Socorro Evangelista (Ambiente Construído, 2017)
Based on historic documents, two lime-based paint formulations were produced in laboratory in order to evaluate their basic characteristics as restoration materials for historic buildings with lime-based components. The paints were made basically with hydrated lime, clay, water and linseed (Linum usitatissimum L.) oil, and one formulation had PVA (polyvinyl acetate)-based glue as fixative, and the other one, Couma guianensis’ latex. Each paint component was characterized by XRD and FTIR, and color and specular gloss measurements were performed on both paints. A preliminary assessment of the paints was conducted using the Pipe Method, the salt crystallization test, visual analysis for dustiness, and analysis of microbiological growth. The results showed that the laboratory-produced paints are theoretically and technologically compatible with lime-based coatings, however, their superficial performance can be improved to achieve greater durability. This study also brings to light local materials from the Amazon region that have great potential to be used and recognized as raw materials for paints and which could also be investigated for other uses.